Removal of lead (pb) by using sulphuric acid H2SO4 treated durian (durio zibethinus) leaf powder / Nurul Aida Abdul Jabar - Abdul Jabar, Nurul Aida (Faculty of Applied Sciences, 2017)
Ability to remove Pb(II) from aqueous solution by sulphuric acid modified durian leaves (SDLP) was evaluated. SDLP was characterized by using pHslurry, pHzpc analysis of biosorbent. The effect of physicochemical such as pH, adsorbent dosage, initial concentration of Pb(II) and contact time had been studied to obtain the optimum condition to remove Pb(II) ion from aqueous solution. The studies were conducted at pH 4 optimum, SDLP dosage 0.03 g, in contact time of 90 minutes and temperature of 30 ᶱC. Kinetic data were analyzed by using two adsorption kinetic models which are pseudo-first-order and pseudo-second-order. The data showed high correlation coefficient based on pseudo-first-order model with R2 between 0.998 to 0.999 rather than pseudo-first-order model